ANALISIS TINGKAT KERAWANAN BANJIR DI KECAMATAN SINGKIL, KABUPATEN ACEH SINGKIL BERBASIS SISTEM INFORMASI GEOGRAFIS - Sadariani, Siti; Edial, Helfia (JURNAL BUANA, 2024)
This research aims to: 1) Analyze the level of flood vulnerability in villages in Singkil District. 2) Analyze the level of flood vulnerability in Singkil District. 3) Knowing the areas flood vulnerability in Singkil District. This research is quantitative research with overlay. The results are: 1) The level of flood vulnerability in villages was obtained a village with the level of non-vulnerable in Selok Aceh 4.15% with area 799.44 ha, vulnerable in Teluk Rumbia 31.21% with area 6006.21 ha, and very-vulnerable in Paya Bumbung 2.42% with area 466.02 ha. 2) The level of flood vulnerability in Singkil Districts based on the results of the analysis, it was found that the level of flood vulnerability not-vulnerable in Singkil District 17.55%, vulnerable 73.24%, and very-vulnerable 9.20%. 3) The area of flood vulnerability in Singkil District is not-vulnerable with area 3,376.48 ha, vulnerable with area 14,087.34 ha, and very-vulnerable with area 1,770.38 ha.